A highly sensitive and selective fluorescent probe based on a Pd-catalyzed reaction for detection of Pd2+. Issue 47 (22nd November 2019) - Du, Man; Zhang, Yue; Yu, Yifeng; Zhao, Hua; Guo, Yue; Yang, Yunxu
Abstract : A novel fluorescent probe for sensitive and selective detection of Pd 2+ based on a Pd-catalyzed reaction has been rationally designed and developed. Abstract : A novel "off–on" fluorescent probe ACBT, using a readily available dye 2-(2′-aminophenyl) benzothiazole as the fluorophore, for the determination of Pd 2+ was designed and synthesized in this work. Based on a palladium triggered cleavage reaction, the probe ACBT exhibited rapid response time (<2 min), and high selectivity and sensitivity towards Pd 2+ in aqueous solution under mild conditions. The detection limit of probe ACBT towards Pd 2+ was estimated to be as low as 2.6 nM. Furthermore, fabrication of probe ACBT test strips was achieved for a convenient visual detection of palladium. In addition, it also has been successfully applied to detect Pd 2+ in environmental water samples with satisfactory results, indicating that the use of probe ACBT could be a potential and feasible method to detect Pd 2+ in environmental systems.